Hubungan Kausal Penalaran Matematis terhadap Prestasi Belajar Matematika pada Materi Bangun Ruang Sisi Datar ditinjau dari Motivasi Belajar Matematika Siswa - Setiawan, Agus (Al-Jabar: Jurnal Pendidikan Matematika, 2016)
This research is a comparative causal research with factorial design 3 3. The population of this study is all students of class VIII SMP Negeri 1 Simpang Pematang. Sampling was done by cluster random sampling. The sample of this research is students of class VIII B and VIII D. Instruments used to collect data is a test of learning achievement, mathematical reasoning test and student motivation questionnaire. Prior to use for data retrieval, achievement test instruments, reasoning tests and motivational questionnaires were first tested in mathematics. Hypothesis test using two way Anava test with unequal cell. The conclusions of this study are: (1) Students with high mathematical reasoning ability have better learning achievement than students with moderate mathematical reasoning ability, students have better learning achievement than students with low mathematical reasoning, and students with ability High mathematical reasoning has better learning achievement than students with low mathematical reasoning ability, (2) Students with high learning motivation have better learning achievement than students with moderate learning motivation, students with high learning motivation have better learning achievement than Students with low learning motivation, and students with learning motivation are having better learning achievement than students with low learning motivation, (3) There is no interaction between mathematical reasoning ability and motivation of learning mathematics to learning achievement Ar math.